The Effect of Health Promotion through Animation Videos on Adolescent's Knowledge related to Drugs Abuse - Vidia Sri Nurani; Aisyiah; Intan Asri Nurani (KHD-Production, 2022)
The prevalence of drugs in Indonesia is increasing every year. It is estimated that 3.8-4.1 million people have used drugs in recent years in the 12–24-year age group. Factors causing drugs in the first subject are internal (personality) and external (peers) factors. In the second subject, namely family factors and living environment. Promotion is needed preventive efforts to increase awareness of adolescents. This study aims to determine the effect of health promotion on adolescent knowledge related to drug abuse in the Middle village area, Kramat Jati sub-district, East Jakarta. Health Promotion through video is one way to overcome initial knowledge about drugs. The purpose of this study was to determine the health effect of using animated videos on adolescent knowledge about drugs in the Middle Village, Kramat Jati sub-district, East Jakarta. The method used is a quasi-experimental, one-group, pre-test design without a control group being used. The sample size is 58 respondents. The sample used is purposive sampling. The instrument in this study was a drug questionnaire, it was validated and reliable with Cronbach's alpha 0.953. The Wilcoxon test was used to test the effect of animated videos on knowledge. The results obtained using the Wilcoxon test showed p=0.000, meaning that health promotion using the effect of animated videos on adolescent knowledge about drugs in Kampung Tengah, Kramat Jati sub-district, East Jakarta